Emphasizing Text Structure Strategy Instruction to Scaffold 11th Grade Students’ Reading Comprehension - Ni Made Andreiya Eliata; Fauzi Miftakh (Journal of Languages and Language Teaching, 2021)
Reading and comprehending an English informational text, always becomes a burdensome activity for Indonesian students. This problem arises not only because of students’ low English language competency, but also insufficient application of traditional reading instruction that teachers teach in regular school. Therefore, this present study has aim to investigate the implementation of Text Structure Strategy as reading instruction to scaffold students’ informational text reading. Due to the COVID-19 outbreak, the learning process of text structure instruction in this study were conducted in the online learning situation. Researchers employed a qualitative case study design with observation as data collection technique. This study involved 33 participants of 11th-grade students on a class in SMA Negeri 1 Cibitung, West Java, Indonesia. Based on Braun and Clarke’s thematic analysis, the result describes that Text Structure Strategy instruction can scaffold learners informational text reading in two main activities, namely introducing the concept of Text Structure Strategy and teaching explicit instruction activity, precisely in modeling and guiding practice.